Collect and disseminate layer protocol for searching cloud services - Arvaree @ Alvar, Thamilvaani (2014)
Cloud computing is one contemporary technology in which the research community has recently embarked. This paradigm shifts the location of the infrastructure to the network to reduce the costs associated with the management of hardware and software resources.In recent years, the number of cloud service providers is increasing. Lack of common cloud standards or protocol delays the interoperability across service providers. Moreover, in capabilities of the search engine to match queries with exact result from service provider is the common issue among cloud users. Thus, lead the cloud customers to face challenges and problems in selecting the right service provider who meets their needs. The objective of this research is to model an approach tha ist able to meet the user’s searches for services in cloud environment whereby the search queries entered by the users can be mapped with accurate cloud services. In meeting this objective, there are two prominent activities proposed by this research. The introduction of the search protocol named Collect Desseminate Layer (CDL) to perform the query matching with high accuracy of search results. The proposed protocol evaluate by developing and implementing a search engine named Cloud Keyword Search Engine (CSSE). Experiments will be designed and conducted to ensure that the protocol meets the specification of matching the search results. The methodology used to enable smooth execution of proposed model going through phases namely preliminary experiments, design activities involving protocol design and tool design and identification of metrics for evaluation and performance analysis experiments. The proposed protocol design is mainly on construction of service searching layer andevaluation and performance analysis experiments for which design to prove the performance of the proposed protocol and search engine. Response time, success rate and similarity ranking are three measurement metrics to be used in this research. Dimensional consistency testing and boundary adequacy testing are two testing strategiesadopted to prove the performance of the proposed protocol and search engine. Results obtained from the analysis of this research show the mapping of an accurate search results as per the user search query using CDL are increasing. The use of proposed protocol and search engine in service searching reduce the time taken to perform the searching. It also recorded that the success rate and similarity ranking of the search results are increased. Results for performance analysis experiments show the performance of protocol is maintained where the computation time remained at constant level even if the number of users are increased. The computation cost is also reduced. The increases of number of users using the search engine at one time is not affecting the Cloud Keyword Search Engine (CSSE) as compared to normal search engine which increases the computation time. Therefore, the proposed model and protocol has able to outperform common search engine process in common protocol in terms of response time, success rate and similarity ranking. It is able to produce a standard protocol and search engine to perform the service searching in cloud computing with high accurate search results to users.